Penatalaksanaan Fisioterapi Kasus Lower back pain e.c Spondylosis Lumbal; Studi Kasus. - Muhammad Fauzan Algifari; Rakhmad Rosadi; Sri Sunaringsih ika Wardojo (Jurnal Ilmiah Fisioterapi, 2022)
Background: Low back pain, also known as LBP, is pain that originates from the lumbar intervertebral disc and is localized to the lumbar region. The symptoms are more evenly distributed and are not limited to one nerve root. Low back pain is discomfort in the lower back caused by nerve issues, muscular irritation, or bone abnormalities. The word spondylosis comes from the Greek word spondylos, which meaning vertebrae. Lumbar spondylosis refers to changes in the spinal joints, such as a rise in intervertebral disc degeneration followed by changes in bone and soft tissue, or it can refer to excessive bone development (osteophytes). The keys to successful patient management are two things: an accurate evaluation to identify what the patient is going through so that treatment goals can be set, and careful knowledge of the individual patient. The goal of this study was to see how successful exercise treatment, manual therapy, stretching, and TENS electrotherapy were at treating Lumbar Spondylosis. Result: After treatment with px tn b, the result of diminishing. There was a decrease in pain with NRS measures at the second meeting, both in motion pain and quiet pain, which had been on motion pain 8 and silent pain 5 at the first meeting, when reviewing the therapy at the second meeting, the findings of motion pain were 5.